Prayers for the People: Homicide and Humanity in the Crescent City - Carter, Rebecca Louise (University of Chicago Press, 2019)
Intro -- Contents -- Introduction: The Crescent City -- Part One: On Fragile Ground -- Clouds -- 1. The Black Urban Delta -- 2. "Twelve Murders and Two Victims?": Asserting Black Social and Spiritual Value -- Part Two: In Search of Love at Liberty Street -- Walk Out There on Faith -- 3. Somebodies on the Battlefield for the Lord -- 4. THOU SHALT NOT KILL: Commanding Peace in Particular Places -- Part Three: Raising Dead Sons -- Seeing -- 5. Black Mothers at the Center of Death and Transformation -- 6. Restorative Kinship: Birthdays and Death Anniversaries for Children of God -- Conclusion: The Crescent City Illuminated -- Acknowledgments -- Notes -- References -- Index.